2022
DOI: 10.1101/2022.07.07.499215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptotagmin 7 outperforms synaptotagmin 1 to promote the formation of large, stable fusion pores via robust membrane penetration

Abstract: Ca2+-triggered exocytosis is a crucial aspect of neuronal and neuroendocrine cell function, yet many of the underlying molecular mechanisms that regulate these processes are unknown. Here, we contrast the biophysical properties of two prominent neuronal Ca2+ sensors, synaptotagmin (syt) 1 and syt7. In both proteins, four Ca2+-binding loops partially penetrate bilayers that harbor anionic phospholipids, and mutagenesis studies suggest that these interactions are important for function. However, these mutations … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Analogously, cholesterol both thickens membranes and favors curvature. We (AHB and AJS) recently found that the thickening preference of cholesterol outweighed its curvature preference, leading to cholesterol depletion at the pore neck (43). Proteins can have a much broader range of membrane interactions compared to cholesterol, and how proteins and lipids work together in the context of a fusion pore is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogously, cholesterol both thickens membranes and favors curvature. We (AHB and AJS) recently found that the thickening preference of cholesterol outweighed its curvature preference, leading to cholesterol depletion at the pore neck (43). Proteins can have a much broader range of membrane interactions compared to cholesterol, and how proteins and lipids work together in the context of a fusion pore is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, experiments with Syt-1 have demonstrated that the tandem C2AB (but particularly C2B) disorders and demixes phosphatidylserine and PI(4,5)P2 chains (12, 42). Recently, Syt-7 was shown to penetrate more deeply into model bilayers than Syt-1, and that this penetration was critical for its function stabilizing fusion pore open states (43). Given that Syt-7 domains interact with strongly curved membranes during fusion, we seek to understand the interplay of induced membrane disordering (thinning), demixing, and curvature stabilization.…”
Section: Introductionmentioning
confidence: 99%